Profile of Generalized Pustular Psoriasis Inpatient Installation at Dr. Moewardi General Hospital Surakarta from January 2018-December 2022 - Hidayati, Nurul; Mulianto, Nurrachmat; Noviani, Laura; Lidjaja, Lifesia Natali (Journal La Medihealtico, 2024)
Generalized pustular psoriasis (GPP) is a form of psoriasis characterised by the presence of sterile pustules. Its prevalence is between 2 and 3.5% of the population worldwide and in Indonesia it is 2.5% of the population. It can cause severe physical and psychosocial distress affecting the patient's quality of life. Objective: To describe the profile of GPP patients treated in the inpatient installation of Dr. Moewardi Hospital, Surakarta in the period of January 2018-December 2022. A retrospective descriptive study was conducted using the secondary data of medical records of GPP patients treated in the inpatient installation of Dr. Moewardi Hospital from January 2018 to December 2022. Results: In the 5-year period, there were 23 GPP inpatients, predominated by female (78.26%) with the age ranged from 5 to 74 years old. Generalised pustular psoriasis mostly affected the age group of 41- 50 years old (26.04%). Most patients were hospitalized for 6–10 days (39.13%). The most common therapy was immunosuppressant (65.2%) followed by oral corticosteroids (26.1%) and zinc (17.4%). Most patients also received moisturizer therapy (56.5%). Generalised pustular psoriasis mostly affects people aged between 41 and 50 years old. Females are more prone to GPP. The therapy given are oral immunosuppressive regimens, oral corticosteroids, zinc, topical corticosteroids and moisturizers.